Inhibition of A2780 Human Ovarian Carcinoma Cell Proliferation by a Rubus Component, Sanguiin H-6 - Lee, Dahae; Ko, Hyeonseok; Kim, Young-Joo; Kim, Su-Nam; Choi, Kyung-Chul; Yamabe, Noriko; Kim, Ki Hyun; Kang, Ki Sung; Kim, Hyun Young; Shibamoto, Takayuki (AMER CHEMICAL SOC, 2016)
The effects of a red raspberry component, sanguiin H-6 (SH-6), on the induction of apoptosis and the related signaling pathways in A2780 human ovarian carcinoma cells were investigated. SH-6 caused an antiproliferative effect and a severe morphological change resembling that of apoptotic cell death but no effect on the cancer cell cycle arrest: In addition, SH-6 induced an early apoptotic effect and activation of caspases as well as the deavage of PARP, which is a hallmark of apoptosis. The early apoptotic percentages of A2780 cells exposed to 20 and 40 mu M SH-6 were 35.39 and 41.76, respectively. Also, SH-6 caused the activation of mitogen-activated protein, kinases (MAPKs), especially p38, and the increase of truncated p15/BID. These results in the present study suggest that the apoptosis of A2780 human ovarian carcinoma cells by SH-6 is mediated by the MAPK p38 and a caspase-8-dependent BID cleavage pathway.
Keywords: CANCER; RESISTANCE; APOPTOSIS; PHENOLICS